A Snapshot Of Energy Production: Opportunities For Coal - Jason Laumb (Rocky Mountain Coal Mining Institute, 2006)
Regional Energy Production ?Energy is a globally traded commodity and is influenced by regional and national needs as well as international trends. We can greatly expand energy export from the region. ?Significant opportunities exist for increased coal-based energy production.